Makings of the sea : journey, doubt and nostalgia - Baldacchino, John (Piscataway, NJ : Gorgias Press, 2010)
Makings of the Sea is an inquiry into the makings of the Mediterranean imagination in the 20th century, focusing on specific cases in the visual and performing arts, music and literature. It also questions a number of populist perceptions of the Mediterranean and its cultures. Following a thematic structure that falls broadly under the headings of journey, doubt and nostalgia, this is an essay on Mediterranean aesthetics.
Frontmatter -- TABLE OF CONTENTS -- ACKNOWLEDGEMENTS -- INTRODUCTION -- 1. TOUCHED HORIZONS -- 2. BODIES OF MEMORY -- 3. PRIVATE SHORES -- 4. A HOLE IN THE SKY -- 5. EVERYDAY'S HERESY -- 6. IN THE POISE OF WATER AND HILL -- 7. ON MEDITERRANEAN AESTHETICS -- BIBLIOGRAPHY -- INDEX
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: National characteristics, Mediterranean -- History -- 20th century; Art and society -- Mediterranean Region -- History -- 20th century; Popular culture -- Mediterranean Region -- History -- 20th century; Political culture -- Mediterranean Region -- History -- 20th century; Aesthetics -- Social aspects -- Mediterranean Region -- History -- 20th century; Mediterranean Region -- Intellectual life -- 20th century; Mediterranean Region -- Social conditions -- 20th century; Mediterranean Region -- Foreign public opinion; Mediterranean Region -- Civilization -- 20th century; Méditerranée, Région de la -- Conditions sociales -- 20e siècle.; Méditerranée, Région de la -- Civilisation -- 20e siècle.; PHILOSOPHY -- History & Surveys -- Ancient & Classical; Aesthetics -- Social aspects; Art and society; Civilization; Intellectual life; National characteristics, Mediterranean; Political culture; Popular culture; Public opinion; Social conditions; Mediterranean Region; 1900-1999; History